Fucosyltransferase 11 restrains ferroptosis via upregulation GPX4 expression in gastric cancer - Bingbing Zhang; Yali Chen; Xuezhou Gu; Yu Zheng; Zhong Hua Jiang (BMC Cancer)
Abstract Ferroptosis is a novel iron-dependent type of programmed cell death that is characterized by the oxidation of lipids by divalent iron ions to produce lipid peroxides, which leads to cell death. Fucosyltransferase 11 (FUT11) is highly expressed in most tumors and is involved in tumorigenesis. However, there have been few studies regarding the relationship between FUT11 and ferroptosis. In this study, we found that FUT11 expression was abnormally high in gastric cancer (GC) cells and that the prognosis of patients with GC and high expression of FUT11 was poor. FUT11 expression was significantly correlated with the TNM stage of GC.Specific knockdown of FUT11 significantly inhibited the proliferation of GC cells, reduced the abundance of the key anti-ferroptotic protein glutathione peroxidase 4(GPX4), induced lipid peroxidation and ferroptosis in GC cells, and inhibited the proliferation of these cells. The overexpression of GPX4 reduced the inhibitory effect of FUT11 on GC cells. In addition, the knockdown of FUT11 significantly inhibited GC tumor growth in mice, and this inhibitory effect was reduced by the overexpression of GPX4. In conclusion, we have shown that FUT11 promotes GC progression by targeting GPX4, thereby inhibiting ferroptosis in GC cells. These findings suggest that FUT11 is a potential therapeutic target for GC.